Do conflito à re-volta: O deslocamento campo-cidade-campo entre camponeses em Alagoas - Lima, Weldja Marques da Silva (2020)
Alagoas has been in the last decades scenario of the growth of agrarian conflicts resulting from the fight for possession and use of land undertaken by peasant families linked to rural social movements. This work seeks to analyze the process of redefinition of the peasant condition associated with the countryside-city-countryside displacements starred by social actors who fight for the conquest of rights in the fight for land. To this purpose, we mobilized search data produced in fieldwork between 2016 and 2019 with peasants who have experienced this transit, and who currently live in camps and settlements in rural areas. From the understanding of motivations of the displacements, it was possible to conclude that the experienced conflicts appears as catalysts of collective and political mobilization, resulting in what we will call as a re-turn to field, insofar as they experience an epistemic and moral gyre, which enable them to recognize themselves as individuals with a landless identity.